Clinical and epidemiological profile of women diagnosed with breast cancer in the state of Bahia (Research, Society and Development, 2022)
This study was structured with the objective of knowing the clinical and epidemiological profile of women diagnosed with breast cancer in the state of Bahia. This is a descriptive, cross-sectional and retrospective study. Data were obtained through the Hospital Cancer Registry (RHC) system of the José Alencar Gomes da Silva National Cancer Institute (INCA). Cases diagnosed and treated in hospitals in Bahia that are part of the RHC system and analytical cases diagnosed with breast cancer (CID c50) in the period from 2015 to 2019 were selected. of 5,649 cases, predominantly in the age group from 40 to 59 years (54.6%), of mixed race (71.6%), with incomplete elementary school (35.1%), residents of Salvador (33.8%), who never used tobacco (71.5%) and alcohol (65%), and who had a family history of cancer (46%). Most of them were diagnosed by histology of the primary tumor (98.9%), with infiltrating ductal carcinoma (76.9%), in the left breast (49.3%) in stage IIA (24.6%), being underwent Surgery (Cir) + Chemotherapy (Qxt) + Radiotherapy (Rxt) (16.3%), who had stable disease after the first treatment (49.4%). However, these data may provide information for planning and improving the actions implemented for prevention and health promotion, taking into account the particularities of each region.